Public Resistance in the National Liberation Movement of Poles in Right-Bank Ukraine in the First Half of the 1860s (From the Central State Historical Archive of Ukraine, Kyiv) - Ivanenko, O. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2021)
The article covers important manifestations and specifics of the protest culture of the Polish community within the South-Western region of the Russian Empire in the first half of the 1860s on the basis of analysis and synthesis of information from the documents of “Office of Kyiv, Podillya and Volyn Governor-General” (f.442) and “Office of the trustee of the Kiev school district” (f.707) of the Central State Historical Archive of Ukraine (Kyiv). Defending one’s own cultural identity as a driver of national development is connected with the awareness of the political interests and goals of the liberation struggle of Poles. The unique influence of the Polish question on historical processes, the configuration of international relations in Europe during the “long 19th century” determines the relevance and scientific significance of the study and thinking of the history of Polish national and cultural movement. Comprehensive study of the Polish question in the European history of the 19th century is an important part of the scientific perception of interethnic contradictions and antagonisms in the Russian Empire and the reaction of European diplomacy and public opinion, a deeper understanding of the essence of Russian-Polish cultural and civilizational confrontation and its impact on Ukrainian national life. Following the three partitions of the Polish–Lithuanian Commonwealth (1772, 1793, 1795) most of the territories of this formerly powerful European state were incorporated into the Russian Empire, there was a fierce struggle for cultural and ideological dominance in the region. The Polish national liberation movement of the 1860s, which culminated in the January Uprising of 1863-1864, developed against a background of broad social and cultural resistance to Russian autocracy, manifested in such protest actions as mourning and serving panikhads for dead Poles, singing patriotic Polish songs and hymns, public wearing of national costumes, participation in anti-government manifestations and demonstrations, refusal to read prayers for the emperor in churches, and so on. Clergy and educators, as well as students and pupils, were the driving force behind this protest movement, which had an international resonance.